Beban-Beban yang Terjadi pada Kuda-Kuda Gedung Parkir Lantai 3 Universitas Tribhuwana Tunggadewi Malang - Ridwan, Muhammad ; Rasidi, Nawir ; Ningrum, Diana (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2018)
Tribhuwana Tunggadewi University Malang has many departments and SMEs, each Department or UKM has its own organizations, so that it requires facilities / places to accommodate every member of the existing organization. The provision of the place must be done by redesigning one of the buildings in the university, namely the 3rd floor parking building shaking the 3rd floor parking building underutilized as a parking lot due to its high building which is located on the 3rd floor. The redesign was done by calculating the strength of the building before and after the building was redesigned and calculating the RAB (planned budget costs) after being redesigned. Profile data is taken / measured directly in the research location, so that secondary data can be obtained either from measurements or interview processes. In the existing condition, the gording uses profile C 75.40.15.3.2 the gording used does not meet the requirements, so the recording is planned to return C 100.50.5. after calculating the load, ie dead load, live load, wind load, analyzing using stadpro is done so that the moments that occur in each direction will be obtained both in the direction of x direction and z direction. In the column, the addition is done in the middle of the portal with profile C 100.50.5 and in each column, the beams are added with a profile of WF 150.75.5.7 to avoid slackness in the center of the portal and can endanger the user above.